Integrodifferential Inequalities Arising in the Theory of Differential Equations - Zareen A. Khan (Abstract and Applied Analysis)
The goal of this paper is to achieve some new results related to integrodifferential inequalities of one independent variable which can be applied as a study of qualitative and quantitative properties of solutions of some nonlinear integral equations.